Investigation of the Enhancement of Heat Transfer in a Flat Plate Solar Collector With a Corrugated Tube Under Thermosiphon Effect - Lopes, Ewerton Ferreira [UNESP]; Salviano, Leandro Oliveira [UNESP] (My University, 2024)
The development of new technologies for energy generation and use has been increasing significantly. In this projection, the use of flat solar collectors to convert solar energy into thermal energy through water heating for residential and commercial purposes has grown due to the potential reduction of up to 40% in electrical energy consumption promoted by these devices. A promising but underexplored area in engineering is the study of the intensification of heat transfer in these devices by changing the dimensional and constructive characteristics of the elevation tubes, especially through a numerical approach by passive systems that operate under the thermosiphon effect. Thus, this work aims to investigate, by using computational fluid dynamics (CFD), the heat transfer process in a flat plate solar collector with a concentric plate to the elevation tube, evaluating different diameters, angles of inclination, and slope corrugation profiles subjected to a constant heat flux. The numerical modeling considers a single-phase, incompressible, permanent, three-dimensional, and laminar flow, in addition to the Boussinesq approximation. The results showed that significant increases in the heat transfer rate can be achieved with absorber plates in comparison to those configurations without absorber plates. Moreover, the increase in the tube diameter allowed gains of up to 5.1% in the heat transfer rate, while the increase in the angle of inclination did not promote significant improvements. The triangular profile R10 P20 configuration increased the Nusselt number by 8%, while the R5 P20 configuration promoted a 25% gain in thermo-hydraulic performance.
Keywords: CFD; corrugated tube; flat plate solar collector; heat transfer; heating; solar energy; thermosyphon effect